2022
DOI: 10.4235/agmr.21.0144
|View full text |Cite
|
Sign up to set email alerts
|

Gastric Cancer in Older Patients: A Retrospective Study and Literature Review

Abstract: Background: With increasing life expectancy, the incidence of gastric cancer (GC) in older adults is increasing. This study analyzed differences in GC characteristics according to age and sex among patients who underwent surgical treatment for GC.Methods: A total of 2,983 patients diagnosed with gastric adenocarcinoma who underwent surgical treatment at Seoul National University Bundang Hospital between 2003 and 2017 were classified into three groups: I (<65 years, n=1,680), II (60–74 years, n=919), and III… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 27 publications
(27 reference statements)
0
11
0
Order By: Relevance
“…Some variables identified as risk factors in this study, including higher ASA PS, higher age, and lower preoperative saturation, were also representative risk factors for PPCs in previous studies. 25 - 27 ) In particular, the latter two are meaningful components of the Assess Respiratory Risk in Surgical Patients in Catalonia (ARISCAT) score, the only validated method for scoring PPCs risk factors. Therefore, efforts to identify risk factors using various methods, such as prospective or large-scale studies, are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…Some variables identified as risk factors in this study, including higher ASA PS, higher age, and lower preoperative saturation, were also representative risk factors for PPCs in previous studies. 25 - 27 ) In particular, the latter two are meaningful components of the Assess Respiratory Risk in Surgical Patients in Catalonia (ARISCAT) score, the only validated method for scoring PPCs risk factors. Therefore, efforts to identify risk factors using various methods, such as prospective or large-scale studies, are necessary.…”
Section: Discussionmentioning
confidence: 99%
“…More than a third of new GC cases are patients aged 75 years and older ( 4 ). Several previous studies have reported that elderly GC patients often show a poorer survival than that of younger patients ( 5 , 6 ). Notably, studies have also found that the overall survival of elderly patients is significantly worse than that of younger patients after gastrectomy ( 7 , 8 ).…”
Section: Introductionmentioning
confidence: 91%
“…They included three different age groups in the study: groups I, II, and III, with ages of < 65 years, 60-74 years, and > 75 years, respectively. Groups II and III showed significantly lower survival, indicating a vital role of age in gastric cancer [ 51 ] . American Society of Clinical Oncology also describes age as one of the risk factors for gastric cancer.…”
Section: Bifidobacterium and Cancer: An Unexplored Controversymentioning
confidence: 99%